Determinant Factor In Decision Making To Become Muslimpreneur - Gunawan, Noviandra; Juliana, Juliana; Adirestuty, Fitranty; Sholahuddin, Muhammad (PT. Student Rihlah Indonesia, 2025)
This research aims to determine and analyze the determinant factors in decision making to become a Muslimpreneur by conducting a survey at the Indonesia Islamic Business Forum, Bandung City. By using the causality method with a quantitative approach, this research analyzed 236 respondents who were members of IIBF Kota Bandung. To prove the hypothesis, the collected data was analyzed using the toolPatrial Least Square - Structural Equation Modeling (PLS-SEM) through the SmartPLS application. This research shows that the variables of interest and level of religiosity influence the decision making to become a Muslimpreneur. This finding confirms that the factors of interest and level of religiosity are very important in encouraging the growth of Islamic entrepreneurship. In order to increase entrepreneurs and Muslimpreneurs in Indonesia, the role of the government and the Muslimpreneur community will be very necessary in socializing and re-promoting the concept of Muslimpreneurs or Islamic Entrepreneurship on various platforms optimally, such as social media, seminars, workshops and several other media. This study is the first in testing the determinant factors of decision making to become a Muslimpreneur in IIBF Bandung City members. This study successfully revealed the strengths and weaknesses of interest factors and levels of religiosity in influencing decision making to become a Muslimpreneur.